Clasificación de documentos científicos mediante técnicas de procesamiento de lenguaje natural y minería de texto - Ortiz Serrano, Yesenia Andreina (2018)
Abstract:The Universidad Técnica Particular de Loja, , with the aim of promoting scientific research, creates groups of research lines to create, socialize research and disseminate in several scientific databases. The articles that are included in the different lines. This degree work aims to determine the relationships between the research lines and the terms of the articles uploaded to SCOPUS from 2003 to 2017; through the collection of information, elaboration of vocabulary, supervised classification, preprocessing and data training. The methodology is the "metametodología", composed of four principles that allow to obtain the result of the proposed research: obtain the result of 623 documents in plain text; Information on the abstract, the author and the keywords of each article was compiled, and a new classification was made due to inconsistencies in the classification. The application of the nearest k algorithms (KNN) and linear discriminant analysis (LDA) shows the accuracy of the classification of the articles, as well as the relationship that exists between them.